Análise comparativa da predação de Toxoptera citricidus (Kirkaldy) e Aphis spiraecola (Patch) (Hemiptera: Aphididae) por artrópodes, em cultura de citros, através da serologia - Costa, Fabiano de Mello (2011)
Citriculture is one of the most important agricultural activities in Brazil, and its production, specially directed to the export of concentrated juice, generates profits that surpass one billion dollars a year. In the present work, specific antisera for Aphis spiraecola (Patch) and Toxoptera citricidus (Kirkaldy) (Hemiptera: Aphididae) were produced, and potential predators of these pests were identified. Serology is based on the possibility of specific reactions between an antiserum obtained for the prey that is going to be investigated and the antigens obtained through the maceration of the possible predators captured in the fields. Samples of the A. spiraecola and T. citricidus aphids were macerated in a 0.75% salt solution. The macerated samples were centrifuged, and the floating ones were used as immunizing antigens for the attainment of the specific antiserum. For that purpose, two rabbits were immunized with doses of antigens in the region of the lymph nodes. Homologous and heterologous serological tests were performed through the method of double diffusion in agar. Homologous serological reactions were positive for both antisera as soon as seven days after the first antigen inoculation. The maximum title between both antisera was of 32. Positive heterologous reactions were observed as for Coccinellidae Azia luteipes (Mulsant), Cycloneda conjugata (Mulsant), Cycloneda sanguinea (Linnaeus), Harmonia axyridis (Pallas), Hippodamia convergens (Guérrin-Meneville), Olla v-nigrum (Mulsant) and Scymnus spp; Chrysoperla externa larvae (Hagen, 1861) (Neuroptera: Chrysopidae), Pseudodorus clavatus larvae (Fabricius, 1794) (Diptera: Syrphidae); one heteropterous (Hemiptera: Heteroptera) and one arachnid (Araneae). No significant differences were observed between C. sanguinea, H. convergens e H. axyridis as for their predatory efficiency. The predators C. sanguinea, H. convergens and H. axyridis did not present differences in their food preference for A. spiraecola or T. citricidus. From the obtained results, one can infer that the predators found in citrus cultivations are potential predators of A. spiraecola and/or T. citricidus and may act as efficient agents of biological control of those aphids, reducing their populations and the damages caused by them. The serological technique used was effective in the detection of predators of those aphids in the fields.